INTEGRATING INTERACTIVE FLASH ANIMATIONS AND JAVA APPLET IN LMS MOODLE - MAGDIN, Martin (Journal of Technology and Information Education, 2010)
The paper discuss about efficient and simple solution to the problem of integrating interactive flash animations and JAVA applet within LMS MOODLE. We created easy-to-use application for generating the HTML code, which is necessary for show files correctly in LMS MOODLE.
Keywords: LMS MOODLE; interactivity; flash animations; JAVA applet; application FlashGen